1992
DOI: 10.1080/02786829208959544
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coating Thickness on Particle Bounce in Inertial Impactors

Abstract: A coating technique for applying uniform, thin layers of grease onto impactor substrates is described. The technique involves dissolving or diluting the grease in a solvent, applying the grease solution to the substrate, the spinning the substrate at a high speed. The coating thickness is controlled by the concentration of grease in the solution and by the spin speed. Apiezon-L vacuum grease and silicone oil were tested with this technique. Coating thicknesses between 0.3 and 9 y m were successfully generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 16 publications
0
50
2
Order By: Relevance
“…Bounce-off can be counteracted by the use of a coating of the impaction surface. Pak et al (1992) showed that a coating of Apiezon-L grease needs to be more than 9 µm thick to obtain close to 100 % impactor collection efficiency for solid particles, whereas silicon oil shows more promising properties with rather high efficiency at 0.3 µm thickness. However, applying such a thickness would result in a factor of 2.5 thicker sampling substrate causing typically a factor 1.6 worse PIXE detection limits (if contamination in the coating process can be avoided).…”
Section: Aerosol Sampling and Analysismentioning
confidence: 99%
“…Bounce-off can be counteracted by the use of a coating of the impaction surface. Pak et al (1992) showed that a coating of Apiezon-L grease needs to be more than 9 µm thick to obtain close to 100 % impactor collection efficiency for solid particles, whereas silicon oil shows more promising properties with rather high efficiency at 0.3 µm thickness. However, applying such a thickness would result in a factor of 2.5 thicker sampling substrate causing typically a factor 1.6 worse PIXE detection limits (if contamination in the coating process can be avoided).…”
Section: Aerosol Sampling and Analysismentioning
confidence: 99%
“…The MOUDI collecting carbonaceous material was operated without rotating the impactor stages, as a multi-orifice impactor (MOI). OC concentrations measured by the carbon analyzer are converted to organic mass (OM) multiplying by a factor of 1.8 to account for the hydrogen, oxygen, sulfur and nitrogen associated with the organic compounds (Turpin and Lim, 2001 Particle bounce-off in cascade impactors has been documented by several authors, particles as small as 0.2 mm can bounce from their respective collection stage and are collected on stages corresponding to smaller sizes (Hinds, 1998;Pak et al, 1992). This problem is more common in the upper stages of the impactors.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that bounce decreases with the coating thickness (Pak et al 1992; Reischl and John 1978). A greased coating with a thickness of a few micron can rapidly become ineffective.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore the substrate must have a large enough capacity to maintain high collection ef ciency, even under heavy loading conditions. Other factors such as the grease coating thickness (Pak et al 1992;Reischl and John 1978), particle hardness (Hinds et al 1999), and shape can also affect bouncing behavior.…”
Section: Design Considerations On Inertial Impactorsmentioning
confidence: 99%